Metaphors of power and propaganda in Lucino T. Sacramento's ang Maharlika and Ang Bituin Concertos for piano and orchestra . - Rempola, Leo Eva
This study focuses on Luciano T. Sacramento's twin concertos for piano and orchestra entilled Ang Maharlika and Ang Bituin. It aims to connect the two works with cultural politics in terms of how power and propaganda were transacted through them during the Marcos regime in 1972-1986. It was during this time that cultural forms like art and music were extensively used to propagate the Marcosian ideologies for the New Society through the pursuit of the true, the good and the beautiful.